A practical multi-objective design approach for optimum exhaust heat recovery from hybrid stand-alone PV-diesel power systems - Yousefi, M.; Kim, J.H.; Hooshyar, D.; Yousefi, M.; Sahari, K.S.M.; Ahmad, R. (Elsevier, 2017)
Integration of solar power and diesel generators (DGs) together with battery storage has proven to be an efficient choice for stand-alone power systems (SAPS). For higher energy efficiency, heat recovery from exhaust gas of the DG can also be employed to supply all or a portion of the thermal energy demand. Although the design of such heat recovery systems (HRSs) has been studied, the effect of solar power integration has not been taken into account. In this paper, a new approach for practical design of these systems based on varying engine loads is presented. Fast and elitist non-dominated sorting genetic algorithm (NSGA-II) equipped with a novel local search was used for the design process, considering conflicting objectives of annual energy recovery and total cost of the system, and six design variables. An integrated power system, designed for a remote SAPS, was used to evaluate the design approach. The optimum power supply system was first designed using the commercial software Hybrid Optimization of Multiple Energy Resources (HOMER), based on power demand and global solar energy in the region. Heat recovery design was based on the outcome of HOMER for DG hourly load, considering different power scenarios. The proposed approach improves the annual heat recovery of the PV/DG/battery system by 4%, PV/battery by 1.7%, and stand-alone DG by 1.8% when compared with a conventional design based on nominal DG load. The results prove that the proposed approach is effective and that load calculations should be taken into account prior to designing HRSs for SAPS.